Frontispiece: Catalytic Ammonia Oxidation to Dinitrogen by Hydrogen Atom Abstraction. Issue 34 (9th August 2019) - Bhattacharya, Papri; Heiden, Zachariah M.; Chambers, Geoffrey M.; Johnson, Samantha I.; Bullock, R. Morris; Mock, Michael T.
Abstract : Ammonia Oxidation A molecular Ru‐based catalyst converts NH3 into N2, as reported by M. T. Mock et al. in their Communication on page 11618 . The cleavage of six N−H bonds was achieved by coupling H + and e − transfers using the t Bu3ArO . radical as the H atom acceptor.